2007
DOI: 10.1128/mcb.01029-07
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of Zona Pellucida Binding Proteins in the Acrosomal Matrix Disrupts Acrosome Biogenesis and Sperm Morphogenesis

Abstract: Zona pellucida binding protein 1 (ZPBP1), a spermatid and spermatozoon protein that localizes to the acrosome, was originally identified in pigs and named for its binding to the oocyte zona pellucida. In an in silico search for germ cell-specific genes, Zpbp1 and its novel paralog, Zpbp2, were discovered and confirmed to be expressed only in the testes in both mice and humans. To study the in vivo functions of both ZPBP proteins, we disrupted Zpbp1 and Zpbp2 in mice. Males lacking ZPBP1 were sterile, with abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(141 citation statements)
references
References 50 publications
3
138
0
Order By: Relevance
“…Putative evidence in the form of co-immunoprecipitation, co-localization, and proximity ligation assays has identified ZP binding protein 2 (ZPBP2) as one of the most compelling client proteins for the CCT/TRiC complex in mature spermatozoa . Originally implicated in secondary ZP binding, a more recent study has shown that male mice null for ZPBP2 are subfertile and display defects in ZP interaction and penetration (Lin et al 2007). In mice, there is additional evidence that certain CCT/TRiC complex subunits are translocated to the sperm surface during sperm capacitation .…”
Section: Multiprotein Complexes In Sperm Capacitation and Zp Interactionmentioning
confidence: 99%
“…Putative evidence in the form of co-immunoprecipitation, co-localization, and proximity ligation assays has identified ZP binding protein 2 (ZPBP2) as one of the most compelling client proteins for the CCT/TRiC complex in mature spermatozoa . Originally implicated in secondary ZP binding, a more recent study has shown that male mice null for ZPBP2 are subfertile and display defects in ZP interaction and penetration (Lin et al 2007). In mice, there is additional evidence that certain CCT/TRiC complex subunits are translocated to the sperm surface during sperm capacitation .…”
Section: Multiprotein Complexes In Sperm Capacitation and Zp Interactionmentioning
confidence: 99%
“…Mammalian ZP glycans contain sulfated sugar residues, and their significance in sperm binding has been implicated (Shimizu et al 1983, Oehninger et al 1991, Mori et al 1993, Yonezawa et al 1995, Howes et al 2001, Howes & Jones 2002, Moreno et al 2002, Dell et al 2003, Gaboriau et al 2007, Lin et al 2007, Topfer-Petersen et al 2008, Yu et al 2009, Pang et al 2011. A number of sulfatases have desulfation activity on sulfated sugar residues (Hanson et al 2004).…”
Section: Wtmentioning
confidence: 99%
“…Genetic manipulations of sperm have often led to unpredictable morphological and physiological changes (Baba et al 1994, Lu & Shur 1997, Nishimura et al 2001, Ensslin et al 2007, Lin et al 2007). Because of these previous problems, some skepticism is warranted about the findings with these in vivo fluorescently tagged sperm (Jin et al 2011).…”
Section: An Alternate Model For Mouse Sperm-zp Binding That Fits the mentioning
confidence: 99%